Systemic barriers to scaling private sector driven climate-smart agricultural innovations in East Africa’s potato, sesame and common bean value chains - Shilomboleni, Helena; Recha, John W.M.; Ubels, Jan; Radeny, Maren A.O.; Solomon, Dawit (2019)
The CRAFT project (2018-2023) promotes a bottom-up market-driven scaling agenda that supports inclusive business models to enhance climate-resilient farming systems through sustainable intensification along selected oilseed, pulse and potato agricultural value chains. The selection criteria for these crops includes sufficient private sector interest and capacity for coinvestment; adequate domestic consumption to drive market development opportunities; and ample evidence of climate change risks projected to face the value chains. Across East Africa, unfavorable climate change patterns involving rising temperatures, increased variability of seasonal rainfall and a higher frequency and intensity of extreme weather events such as droughts and floods are aggravating food insecurity and pose further challenges for rural development (Government of Kenya 2018).